2021
DOI: 10.3889/oamjms.2021.5778
|View full text |Cite
|
Sign up to set email alerts
|

Family Support in Caring for Diabetes Mellitus Patient: Patient’s Perspective

Abstract: BACKGROUND: Perspectives of diabetes mellitus patients on family support received during the treatment of their disease at home has high complexity. The family’s intention to help patients to take care of themselves at home can lead to misperceptions or is not well accepted by diabetes mellitus patients. AIM: The aim of the study was to explore the support provided by families in the care of diabetes mellitus patients at home based on the patient’s perspective. METHODS: A phenomenological study using semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Participants in this study reported that they get support from their family members in the form of collection of medication, and preparation and serving of food or meals. The ndings of this study are consistent with Indonesian study which reported that patients living with diabetes get support at home from family members they resides with [21]. Provision of support to family members living with diabetes within African culture could be attributed to the concept of botho or humanity.…”
Section: Discussionsupporting
confidence: 89%
“…Participants in this study reported that they get support from their family members in the form of collection of medication, and preparation and serving of food or meals. The ndings of this study are consistent with Indonesian study which reported that patients living with diabetes get support at home from family members they resides with [21]. Provision of support to family members living with diabetes within African culture could be attributed to the concept of botho or humanity.…”
Section: Discussionsupporting
confidence: 89%
“…Study interviewees reported receiving support from their family members, in the form of collection of medication, and preparation and serving of food or meals. The findings of this study are consistent with an Indonesian study which reported that diabetes patients were supported at home, by family members they lived with [22]. Nutrition and exercise, including medication use or insulin injection are essential in the management of diabetes for all age groups and gender [18,23].…”
Section: Discussionsupporting
confidence: 89%
“…Chronic non-communicable diseases are diseases that are not transmitted and progress slowly over a long period. In the early stages, non-communicable diseases often do not show symptoms, so many do not know and realize that they have suffered from the disease because of a lack of awareness from the public to carry out early detection of the disease (Wulandari, 2021). When the disease has complications and even death, people tend to carry out examinations.…”
Section: Introductionmentioning
confidence: 99%
“…The support most needed by sufferers is from the nuclear family, namely their spouse and children, who live with the sufferer and those who live near their home. People with chronic diseases whom their families support will feel stronger, more grateful, and able to accept their disease conditions (Wulandari, 2021). In addition, to support from the family, the patient's motivation will significantly affect the sufferer's quality of life.…”
Section: Introductionmentioning
confidence: 99%